2008
DOI: 10.1124/dmd.108.021907
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Drug-Drug Interactions From in Vitro Induction Data

Abstract: ABSTRACT:Cytochrome P450 induction-mediated drug-drug interaction (DDI) is one of the major concerns in clinical practice and for the pharmaceutical industry. Previously, a novel approach [the relative induction score (RIS)] was developed using the Fa2N-4 immortalized human hepatocyte line and proposed as a tool for predicting magnitude of clinical DDIs caused by induction of CYP3A. The approach is based on combining in vitro induction parameters (EC 50 and E max ) with the efficacious free plasma concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Additional analysis could include assessing compound CYP induction potential, for example, the relative induction score (RIS) where EC 50 and E max values are utilized, although these methods often require clinical data (e.g., plasma concentration of inducer corrected for protein binding), which may not be available for all compounds. 31 Thus, we have shown that CYP-inducing compounds can be predicted using our 3D model in an automated multiplexed assay system, although more optimization and validation may be required to improve sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Additional analysis could include assessing compound CYP induction potential, for example, the relative induction score (RIS) where EC 50 and E max values are utilized, although these methods often require clinical data (e.g., plasma concentration of inducer corrected for protein binding), which may not be available for all compounds. 31 Thus, we have shown that CYP-inducing compounds can be predicted using our 3D model in an automated multiplexed assay system, although more optimization and validation may be required to improve sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a number of in vitro systems have been used to predict the magnitude of rifampin induction in vivo (Fahmi et al, 2008b;Shou et al, 2008;Galetin et al, 2010). Whereas hepatocytes are considered the "gold standard," both HepaRG and Fa2N-4 have been proposed as appropriate surrogates for assessment of CYP3A4 induction (Fahmi et al, 2008a;Hariparsad et al, 2008;McGinnity et al, 2009). However, in vitro induction data vary greatly between in vitro systems ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration-dependent change in either CYP3A4 expression (mRNA or protein) or function (enzyme-specific substrate metabolism) can be modeled to estimate potency (EC 50 ) and magnitude (E max ) of induction in vitro. Primary and cryopreserved human hepatocytes and the immortalized liver cell lines Fa2N-4 and HepaRG are four in vitro systems commonly used to estimate EC 50 and E max (Fahmi et al, 2008a;Hariparsad et al, 2008;McGinnity et al, 2009). The data from these in vitro systems have been shown to be predictive of in vivo drug metabolism; however, each system has its own characteristics that may influence the induction parameter obtained (Vermeir et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Predictive mathematical models incorporating either induction alone or induction in combination with inhibition mechanisms have been applied by a number of authors (Fahmi et al, 2008b;Shou et al, 2008;Fahmi and Ripp, 2010;Kirby et al, 2011;Templeton et al 2011). Dynamic models based on an inducer concentration-time profile to account for the change in enzyme expression have also been proposed (Almond et al, 2009;Fahmi et al, 2009).…”
Section: Introductionmentioning
confidence: 99%